PEMAHAMAN BUDAYA PENUTUR ASING DALAM PEMBELAJARAN PENERJEMAHAN UNTUK MENGURANGI KESALAHAN PENERJEMAHAN DARI BAHASA INDONESIA KE BAHASA INGGRIS - Siyaswati, Siyaswati; Bandjarjani, Wahju; Oediarti, Joesasono (LPPM Universitas PGRI Adi Buana Surabaya, 2013)
The aim of this descriptive qualitative research is to investigate the effectiveness of thecomprehension of the students of 6th semester batch 2010 of the English Department, Faculty ofTeacher Training and Education, Universitas PGRI Adi Buana Surabaya of the cultural awarenessof English native speakers to reduce errors in translating Indonesian texts into English ones. Theproblems faced by the students are their lacks of the cultural awareness of the English nativespeakers shown by the previous translation test result. Students often do not follow what DellHymes refers by Ã¢â‚¬Å“Cultural AwarenessÃ¢â‚¬Â(1972) as examples in knowledge of the forms andexpressions used in the culture of English native speakers. The cultural awareness was given byintroducing the cultural expressions of English native speakers, especially the awareness of theEnglish proverbs, sayings, and idiomatic expressions. This research chose 35 samples takenpurposively. The research used one group pre-test post-test design. After students were given thecultural awareness, 17 students achieved good marks, above the passing grade 70. They, in fact,perform well in translating Indonesian texts into English ones. Eight students scored below 70 and10 students did not have valid data, so they could not be analyzed. It could be concluded thatstudentsÃ¢â‚¬â„¢ cultural awareness of English native speakers could help them to translate Indonesiantexts into English ones.